Serping1/C1 Inhibitor Affects Cortical Development in a Cell Autonomous and Non-cell Autonomous Manner - Gorelik, Anna; Sapir, Tamar; Woodruff, Trent M.; Reiner, Orly (Frontiers in Cellular Neuroscience, 2017)
Current knowledge regarding regulation of radial neuronal migration is mainly focused on intracellular molecules. Our unbiased screen aimed at identification of non-cell autonomous mechanisms involved in this process detected differential expression of Serping1 or C1 inhibitor, which is known to inhibit the initiation of the complement cascade. The complement cascade is composed of three pathways; the classical, lectin, and the alternative pathway; the first two are inhibited by C1 inhibitor, and all three converge at the level of C3. Knockdown or knockout of Serping1 affected neuronal stem cell proliferation and impaired neuronal migration in mice. Knockdown of Serping1 by in utero electroporation resulted in a migration delay of the electroporated cells as well as their neighboring cells demonstrating a non-cell autonomous effect. Cellular polarity was also affected. Most importantly, expression of protein components mimicking cleaved C3 rescued the knockdown of Serping1, indicating complement pathway functionality. Furthermore, we propose that this activity is mediated mainly via the complement peptide C5a receptors. Whereas addition of a selective C3a receptor agonist was minimally effective, the addition of a dual C3aR/C5a receptor agonist significantly rescued Serping1 knockdown-mediated neuronal migration defects. Our findings suggest that modulating Serping1 levels in the developing brain may affect the complement pathway in a complex way. Collectively, our findings demonstrate an unorthodox activity for the complement pathway during brain development.